A Tropical Conservation Priority Index (TCPI) as an integrative ecological framework with application to Lantana camara - SUTOMO SUTOMO; HENDRA HELMANTO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Sutomo, Helmanto H. 2026. A Tropical Conservation Priority Index (TCPI) as an integrative ecological framework with application to Lantana camara. Biodiversitas 27 (7): d270704. https://doi.org/10.13057/biodiv/d270704. Conservation prioritization in tropical ecosystems is often based on individual ecological metrics, which may not fully capture the complexity of species-environment relationships. Although species distribution models and conservation assessment tools are widely used, frameworks integrating multiple ecological dimensions into a single prioritization metric remain limited. This study presents the Tropical Conservation Priority Index (TCPI), an exploratory ecological framework integrating Habitat Suitability (HS), Spatial distribution structure (R), Ecological Tolerance (ET), and Environmental Drivers (ED) into a composite metric for preliminary ecological assessment in conservation and management contexts. As a proof-of-concept, the framework was applied to Lantana camara using species occurrence records, environmental raster layers, and field-based vegetation and environmental data from several conservation areas in Indonesia. Habitat suitability was estimated using MaxEnt, spatial structure was represented by Extent of Occurrence (EOO) and Area of Occupancy (AOO) derived from GeoCAT, ecological tolerance was approximated from SDM response-curve ranges, and environmental drivers were assessed using Canonical Correspondence Analysis (CCA). The resulting TCPI value for L. camara was 0.591, categorized as moderate-to-high under the exploratory classification scheme. This value reflected broad spatial occupancy, modeled environmental response breadth, and environmental associations observed in field data. Because several components were derived from related analytical structures, the index should be interpreted cautiously as an exploratory integrative exercise rather than a fully validated operational prioritization tool. The analysis also highlights that TCPI interpretation depends on ecological context. For native or threatened taxa, higher values may indicate conservation priority, whereas for invasive species they may reflect management urgency. Although further validation, calibration, and benchmarking across taxa and ecosystems are needed, the framework provides an initial basis for methodological refinement and ecological comparison.